MONITORING VARIABILITAS DARI PROSES SHORT DAN LONG RUN - Muhammad Mashuri (STATISTIKA: Forum Teori dan Aplikasi Statistika, 2004)
One of the problems in the quality improvement is variability monitoring, in such a way so it remains on the threshold. Themain problem in the implementation of process variability monitoring is the parameter estimation before the processproduction is run. . In the short run process or long run process on start up stage the problem is difficult to handle. Thispaper discusses an approach, which enables to do the process variability monitoring for short or long run processes,without historical data for parameter estimation. An illustration of comparison clarifies the mechanism of our discussion.